2012
DOI: 10.1186/1471-2458-12-111
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-specific population attributable risks of metabolic disorders on all-cause and cardiovascular mortality in Taiwan

Abstract: BackgroundThe extent of attributable risks of metabolic syndrome (MetS) and its components on mortality remains unclear, especially with respect to age and gender. We aimed to assess the age- and gender-specific population attributable risks (PARs) for cardiovascular disease (CVD)-related mortality and all-cause mortality for public health planning.MethodsA total of 2,092 men and 2,197 women 30 years of age and older, who were included in the 2002 Taiwan Survey of Hypertension, Hyperglycemia, and Hyperlipidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
5
37
1
Order By: Relevance
“…The prevalence of diabetes in this population was 6.8%, which was comparable with the prevalence of diabetes in two previous Taiwan studies, ranging from 7.8 to 9.1% (Chang et al, 2010;Wang et al, 2012). Median PFOA, PFOS, PFNA, PFUA was 8.0, 3.2, 3.8 and 6.4 ng/ml, respectively (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…The prevalence of diabetes in this population was 6.8%, which was comparable with the prevalence of diabetes in two previous Taiwan studies, ranging from 7.8 to 9.1% (Chang et al, 2010;Wang et al, 2012). Median PFOA, PFOS, PFNA, PFUA was 8.0, 3.2, 3.8 and 6.4 ng/ml, respectively (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…Abdominal obesity is a predictor for developing MetS for both men and women, 23 but women with obesity had higher CVD mortality. 24 Hokanson and Austin 25 reported that high triglyceride levels increased CVD risks greater in women than in men (relative risks, 1.76 versus 1.32). In patients who had received coronary artery bypass graft surgery, women with elevated triglyceride levels had a greater risk than men (hazard ratio, 1.5 versus 1.1).…”
Section: Discussionmentioning
confidence: 97%
“…Concerning hospitalization of CHD, hypertension also demonstrated the highest PAR in women (43%). In several recent studies performed in different continents and ethnics, hypertension was also the most important factor in cardiovascular burden [26][27][28][29][30][31], the agestandardized cardiovascular mortality attributable to higher-than-optimal SBP ranged from 200 to 220 per 100 000 to 410 per 100 000 for men in different parts of USA [32], and the lack of control contributed largely to the risk [27]. The present data stress the necessity for the primary prevention of hypertension as well as improvement in blood pressure control.…”
Section: Discussionmentioning
confidence: 99%